Analisis problematika santri tahfidz alquran di pondok pesantren raudlatul fatah puspan maron probolinggo: Analisis problematika santri tahfidz alquran di pondok pesantren raudlatul fatah puspan maron probolinggo - Sukir, Zahratul ummah; Humaidi; Baharuddin (IAIN Ambon, 2025)
Memorizing the Qur'an is not easy, there are so many obstacles faced by students. The study intends to identify the problems of students in memorizing the Qur'an and provide solutions to make the memorization process easier. This study was conducted at the Raudlatul Fatah Puspan Maron Probolinggo Islamic Boarding School, by implementing qualitative research and a descriptive approach. Data were obtained through interviews, observations and documentation. Interviews were conducted with several students and ustads at the Raudlatul Fatah Puspan Maron Islamic Boarding School. The study findings suggest that the problems of students memorizing the Qur'an were internal (internal) and external (external) problems, for example internal problems are 1) Laziness in students 2) difficulty in managing time 3) and lack of concentration, while external problems are 1) environmental influences 2) busy activities 3) lack of support from the family also greatly influences students 4) peer factors. From various problems that exist, researchers provide solutions to handle the problems of students memorizing the Qur'an by fighting laziness with motivation, providing easy methods. And finally, evaluation to find out the development of students' memorization. The conclusion is that students face problems from internal and external factors, and are given solutions to overcome problems and also provide strong methods to strengthen memorization such as the talaqqi, takrir, murojaah methods. and evaluation is carried out through routine tahsin, murojaah and munaqosya exams every year.